Implementasi Progam Peningkatan Pemahaman Masyarakat Nagari Pariangan Dalam Penaggulangan Bencana Dan Evakuasi Tahun 2023 - Fajar Algifahri Jofe; Irvan Rinaldi; Ksatria Nugraha; Miradzi Ma’ruf; Rahmadani Yusran (Lembaga Pengembangan Kinerja Dosen, 2023)
There are 10 percent of Indonesian people who live around the slopes of volcanoes. One of the areas in Indonesia that has an active volcano is in the province of West Sumatra, namely Mount Marapi which is located between the districts of Tanah datar and the city of Bukittinggi. The risk of loss of life in the event of an eruption or eruption of Merapi in the future will have a high risk of loss of life if the people and tourists of Village Pariangan do not understand disaster mitigation and evacuation. in analyzing details to provide an overview of community understanding of mitigation and evacuation with a Likert scale then unification of activities to increase community understanding in terms of mitigation and evacuation such as community empowerment, infrastructure improvement, and so on with related agencies around village Pariangan. By holding regular evacuation training and simulations for the community. It is hoped that people's understanding of disaster mitigation and evacuation can increase and be better prepared in dealing with future disaster risks.